Implementation of Flora and Fauna-Based Smart Word Learning Media to Empower Elementary School Students' Motivation and Science Literacy: Implementasi Media Pembelajaran Kata Pintar Berbasis Flora dan Fauna untuk Memberdayakan Motivasi dan Literasi Sains Siswa SD - Asy’ari; Fitriyah, Lailatul; Putra, Deni Adi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to develop learning media based on Flora and Fauna to increase motivation and scientific literacy at the elementary level, especially at SD Negeri Latsari IV Tuban. This smart word learning media is a two-dimensional teaching aid. This research uses descriptive research with a qualitative approach. This study resulted in a Flora and Fauna-based learning media for Smart Words for elementary school children. The making of learning media is made of easily available materials such as cardboard, paperboard, and HVS paper, letters and also ordinary printed pictures. The results of the research data analysis used questionnaire data analysis, interview data analysis, observation data analysis and documentation data analysis. In the percentage of the results of the application of the Flora and Fauna based Smart Words learning media, 87% of students are happy with the learning process and with this learning media, students become more enthusiastic in learning. The Flora and Fauna-based Smart Word learning media is very suitable to be applied in learning, especially at the elementary level. This learning media is able to increase students' interest in learning and students' motivation in studying Flora and Fauna so that it becomes a fun learning process, as well as increasing the variety of learning media in the classroom.